The compliance approach for analyzing biomaterial interface cracks - Abdel-Fattah, Hisham; Hamoush, Sameer A. (Computer Assisted Methods in Engineering and Science, 2023)
A numerical method is presented for analyzing the mixed mode interface crack between two dissimilar isotropic materials. A simple and efficient solution procedure is developed based on the finite element method and the compliance approach in conjunction with the fundamental relations in fracture mechanics. The procedure makes it possible to separate the Mode I and Mode II stress intensity factors KI and KII respectively for an interfacial crack in bi-material media under different loading conditions. The strain energy release rate is first computed, then using the compliance method and the known auxiliary solutions, the values for KI and KII are evaluated. The procedure is investigated for different crack extensions. The formulations used for computing the strain energy release rate and the stress intensity factors are presented . The method converges to accurate solutions for small crack extensions. A numerical example is presented to demonstrate the accuracy of the proposed model.